Current Expected Credit Losses (CECL) Standard and Banks’ Information Production - Kim, Sehwa; Kim, Seil; Kleymenova, Anya; Li, Rongchen (The Accounting Review, 2026)
ABSTRACT We examine whether the adoption of the current expected credit losses (CECL) model, which incorporates forward-looking information in loan loss provisions (LLPs), enhances banks’ information production. Consistent with better information production, we document significant changes in both financial reporting and operational outcomes following CECL adoption. First, CECL banks’ LLPs become timelier and better reflect future local economic conditions. Second, CECL banks experience lower rates of loan defaults. These improvements are more pronounced among banks that invest more in CECL-related information systems and human capital, and are especially salient for larger banks. Our findings suggest that forward-looking accounting standards can enhance banks’ information environments. JEL Classifications: E32; G2; G28; M4; M48.